Challenges to large-scale digital organization: the case of Uber - John M. Jordan (Journal of Organization Design, 2017)
Mobile computing, the so-called Internet of Things, and the rapid expansion of Internet connectivity all over the world are combining to challenge long-standing assumptions about the mission, function, and reach of traditional organizational forms. Uber is a fast-growing company with several unique attributes: its drivers are not employees, the company does not own the majority of its productive infrastructure, and the management is often at odds with local law and custom. Uber's rapid rise to unprecedented scale serves to illustrate the gaps between traditional organizational assumptions and the reach of current technological capability. To address these gaps, we conclude by suggesting four principles for designing large-scale digital organizations.
Keywords: 650; Uber; Coordination costs; Algorithmic decision-making; Designing digital organizations; Organizations as culture processors